The breakup of Old English to-infinitive: Causes and consequences - Jarad, Najib (Studia Anglica Posnaniensia, 2012)
The main goal of this paper is to account for the recategorisation of the Old English to-infinitive and the consequent rise of for before the Middle English to-infinitive. We argue that the loss of D feature has two consequences. The first consequence is that V?to-D movement was lost resulting in the break-up of the (morphological and) syntactic unity of the to-infinitive. The second consequence, a consequence of the first consequence, concerns the appearance of the so-called split infinitive, i.e. the development of a preverbal adverb, negation and object position. This crucial evidence marks the drift of the infinitive towards VP behaviour. Given that D was lost in early Middle English (i.e. 1150-1200) and the split infinitive appeared in the 13th century, the paper concludes that the change from a PP to a TP status was gradual and not simultaneous with other changes.